The relationship of participative leadership and psychological safety on employee performance: a case study at PT Suprabakti Mandiri - M., Felix R. M. Hamonangan; Hendarman, Achmad Fajar (Priviet Social Sciences Journal, 2026)
This study investigates the relationships between participative leadership, psychological safety, and employee performance at PT Suprabakti Mandiri, an engineering services and maintenance company operating in a high-risk, quality-sensitive environment. Using a quantitative, cross-sectional correlational design, data were collected from 270 employees across core operational departments via an online structured questionnaire. Instrument quality was confirmed through item validity testing, where all items exceeded the critical correlation threshold, and reliability analysis, which indicated strong internal consistency for participative leadership (α ≈ 0.85 0.87), psychological safety (α ≈ 0.70 0.73), and employee performance (α ≈ 0.77 0.79) constructs. Classical assumption tests supported the suitability of linear regression, with residuals normally distributed, no multicollinearity (VIF = 1.281), no heteroscedasticity, and linear relationships between the predictors and outcomes. The regression results show that participative leadership is positively and significantly associated with employee performance (p < 0.001; R² = 0.254). Psychological safety also demonstrated a positive and significant relationship with employee performance and explained a larger share of variance (p < 0.001; R² = 0.392). When tested jointly, participative leadership and psychological safety remained significant predictors and collectively explained 44.9% of the performance variance (p < 0.001; R² = 0.449), with psychological safety showing a stronger standardized effect. These findings suggest that improving leadership participation and strengthening psychological safety may enhance performance consistency and support efforts to reduce recurring non-conformance outcomes in contractor-based engineering operations.